A neurobiological link between transportation noise exposure and metabolic disease in humans. (September 2021) - Osborne, Michael T.; Naddaf, Nicki; Abohashem, Shady; Radfar, Azar; Ghoneem, Ahmed; Dar, Tawseef; Wang, Ying; Patrich, Tomas; Oberfeld, Blake; Tung, Brian; Pitman, Roger K.; Mehta, Nehal N.; et al.
Abstract: Background: Chronic transportation noise exposure associates with cardiovascular events through a link involving heightened stress-associated neurobiological activity (as amygdalar metabolic activity, AmygA) on 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG-PET/CT). Increased AmygA also associates with greater visceral adipose tissue (VAT) and type 2 diabetes mellitus (DM). While relationships between noise exposure and VAT and DM have been reported, the underlying mechanisms remain incompletely understood. We tested whether: (1) transportation noise exposure associates with greater (a) baseline and gains in VAT and (b) DM risk, and (2) heightened AmygA partially mediates the link between noise exposure and these metabolic diseases. Methods: VAT was measured in a retrospective cohort (N = 403) who underwent clinical 18 F-FDG-PET/CT. AmygA was measured in those with brain imaging (N = 238). Follow-up VAT was remeasured on available imaging (N = 67). Among individuals (N = 224) without baseline DM, incident DM was adjudicated over 2 years from clinical records. Noise (24-h average) was modeled at each individual's home address. Linear regression, survival, and mediation analyses were employed. Results: Higher noise exposure (upper tertile vs. others) associated with greater: baseline VAT (standardized β [95% confidence interval (CI)] = 0.230 [0.021, 0.438], p = 0.031), gains in VAT (0.686 [0.185, 1.187], p = 0.008 adjusted for baseline VAT), and DM (hazard ratio [95% CI] = 2.429 [1.031, 5.719], p = 0.042). The paths of: ↑noise exposure→↑AmygA→↑baseline VAT and ↑noise exposure→↑AmygA→↑subsequent DM were significant (p < 0.05). Conclusions: Increased transportation noise exposure associates with greater VAT and DM. This relationship is partially mediated by stress-associated neurobiological activity. These findings suggest altered neurobiology contributes to noise exposure's link to metabolic diseases. Graphical Abstract: ga1 Highlights: Noise exposure associates with greater baseline and gains in visceral adiposity. Noise exposure also associates with greater diabetes risk over 2 years. Noise exposure's link to these diseases involves altered neurobiological activity. These findings suggest novel therapies for metabolic disease due to noise exposure.